2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091027
|View full text |Cite
|
Sign up to set email alerts
|

The impact of shoulder abduction loading on EMG-based intention detection of hand opening and closing after stroke

Abstract: Many stroke patients are subject to limited hand functions in the paretic arm due to a significant loss of Corticospinal Tract (CST) fibers. A possible solution for this problem is to classify surface Electromyography (EMG) signals generated by hand movements and uses that to implement Functional Electrical Stimulation (FES). However, EMG usually presents an abnormal muscle coactivation pattern shown as increased coupling between muscles within and/or across joints after stroke. The resulting Abnormal Muscle S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…Decoding EMG signals for neural machine interface is a great challenge in the individuals with chronic hemiparetic stroke due to prevalent motor deficits, such as flexion synergy (Lan et al, 2011 ; Yao et al, 2015 ). Many studies made great efforts acquiring better quality of EMGs or features to improve the overall classification accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decoding EMG signals for neural machine interface is a great challenge in the individuals with chronic hemiparetic stroke due to prevalent motor deficits, such as flexion synergy (Lan et al, 2011 ; Yao et al, 2015 ). Many studies made great efforts acquiring better quality of EMGs or features to improve the overall classification accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that after a stroke synergy-induced EMG signals from the impaired hand can reach to a significant level with increased shoulder abduction (SABD) loading, even when a study participant was instructed to relax the hand (Miller and Dewald, 2012 ). These synergy-induced EMGs do not represent the intention of hand movements and thus are detrimental to the accurate classification of volitional hand movements (Lan et al, 2011 ). For example, when the impaired arm was fully supported, i.e., no effect of flexion synergy, the classification of hand movements can reach an overall accuracy of 96% with high-density myoelectric recordings (Zhang and Zhou, 2012 ), or 95% with bipolar surface EMG recordings (Lan et al, 2011 ), but when lifting the paretic arm, the overall accuracy drops by 10 to 16% using EMG signals (Lan et al, 2011 ) or using EEG signals (Yao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…3134 Increased abduction of the shoulder is associated with an increase in involuntary elbow, wrist, and finger flexor synergy. 35,36 Preliminary studies from our lab found that facilitating scapular mobilization and external rotation can decrease spasticity in the entire upper arm and increase the available range in shoulder external rotation, and elbow, wrist and finger extension. 37 Thus strengthening the muscles that restore scapulo-humeral rhythm may avoid abnormal arm movement patterns and facilitate learning of desirable movements.…”
Section: Discussionmentioning
confidence: 99%
“…As the lesions become larger and cause neural damage beyond these areas, the overall picture of loss of fractionated finger movements is similar (Raghavan et al, 2006 ). Even in people who are severely affected poststroke, one can see abnormal synergistic control, as indicated by coactivation and more stereotypic movement patterns across the entire arm (Lan et al, 2011 ; Miller and Dewald, 2012 ). The degree of pathological synergy (i.e., loss of fractionated movement) is consistently correlated with the loss of functional upper limb ability, regardless of the specific subpopulation studied and/or the methods for quantifying synergistic movements and function (Bourbonnais et al, 1989 ; Lang and Schieber, 2003 , 2004 ; Raghavan et al, 2006 ; Lang and Beebe, 2007 ; Beebe and Lang, 2008 ; Miller and Dewald, 2012 ; Ohn et al, 2013 ).…”
Section: Effects Of Various Pathologies On the Presence And Control Omentioning
confidence: 99%